2012
DOI: 10.1371/journal.pone.0040365
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Microgravity on Human Umbilical Vein Endothelial Cell Angiogenesis and Role of the PI3K-Akt-eNOS Signal Pathway

Abstract: Endothelial cells are very sensitive to microgravity and the morphological and functional changes in endothelial cells are believed to be at the basis of weightlessness-induced cardiovascular deconditioning. It has been shown that the proliferation, migration, and morphological differentiation of endothelial cells play critical roles in angiogenesis. However, the influence of microgravity on the ability of endothelial cells to foster angiogenesis remains to be explored in detail. In the present study, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 47 publications
5
65
0
Order By: Relevance
“…The expression and phosphorylation at the Ser 1177 site of eNOS are important to maintain the endothelial cell function (28,31). Protein kinase Akt can phosphorylate eNOS directly on serine 1179 (1177) and activate the enzyme, leading to NO production (15,21,40). The activity of the Akt/eNOS pathway represents the endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…The expression and phosphorylation at the Ser 1177 site of eNOS are important to maintain the endothelial cell function (28,31). Protein kinase Akt can phosphorylate eNOS directly on serine 1179 (1177) and activate the enzyme, leading to NO production (15,21,40). The activity of the Akt/eNOS pathway represents the endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…However, after 24 h of clinorotation, tube formation and migration as well as endothelial nitric oxide synthase (eNOS) activity of human umbilical vein endothelial cells were significantly increased, suggesting an s-mg-mediated promotion of angiogenesis via the PI3K-Akt-eNOS pathway. 93 In addition, Wang et al showed that clinorotation also upregulated inducible NOS (iNOS) in an AP-1-dependent manner and suggested a possible involvement of this pathway in the development of postflight orthostatic intolerance. 94 In parallel to observations in r-mg, the cytoskeleton of ECs grown on the clinostat was remodeled.…”
Section: 83mentioning
confidence: 99%
“…Results concerning the effects of mechanical stress on the assembly of ECs into capillary-like structures in vitro are still poorly understood. For instance, simulated microgravity conditions have been reported to enhance capillary-like structure formation by HUVECs cultured in matrigel [37]. Nonetheless, considering microgravity and hypergravity as having opposite effects is not a straightforward conclusion [8].…”
Section: In Vitro Angiogenesis Under Hypergravitymentioning
confidence: 99%